Answer:
The correct option is:
h(x)=f(g(x)), where f(x)=x2 and g(x)=3x−5
Step-by-step explanation:
We have the function
![h(x)=(3x-5)^2](https://img.qammunity.org/2023/formulas/mathematics/college/94xamk438c7kwfi1avb8h2oez4rw1ba5c3.png)
And we want to find the functions f and g such that:
![h(x)=f(g(x))](https://img.qammunity.org/2023/formulas/mathematics/college/kdwcay27jofvlpj1xhfa44hlk4klj0s1m4.png)
We can see that in h(x) we have a parenthesis squared. If we define f as:
![f(x)=x^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/ggqp4tf9ahbsgqhvjmgpjcoq74fanvke01.png)
Then, the function f will square whatever we put in the function.
Now if we define:
![g(x)=3x-5](https://img.qammunity.org/2023/formulas/mathematics/college/eqv8w23sqnongjr6scuohmvggh4s2488dq.png)
Now, if we evaluate f(x) on g(x):
![f(g(x))=(g(x))^2=(3x-5)^2=h(x)](https://img.qammunity.org/2023/formulas/mathematics/college/7mv5377lwfm4u4h1sbrhxjeqia9ch4ims1.png)
Thus, the correct answer is the first option